2013
DOI: 10.1159/000346679
|View full text |Cite
|
Sign up to set email alerts
|

Association between Neuropeptide Y Gene Polymorphisms and Alcohol Dependence: A Case-Control Study in Two Independent Populations

Abstract: Background: Alcohol dependence is a chronic, progressive neurobiological brain disorder. Previous research reported an inverse association between ethanol drinking and cerebral neuropeptide Y (NPY) levels. There are conflicting results of studies on NPY gene polymorphisms in association with alcohol dependence in humans. Methods: To assess the role of the NPY gene in alcohol dependence, we genotyped three polymorphisms - in a sample of 195 subjects from the Kota population (80 alcohol dependence and 115 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 90 publications
0
12
0
5
Order By: Relevance
“…153 The G1258A polymorphism of the NPY gene has been linked to alcohol dependence. 154 The rs16147 SNP of the NPY promoter gene was linked to tobacco addiction. 155 Should a medication become available that modulates CRF or NPY, such genetic analysis may reveal that subpopulations of subjects who carry specific SNPs might be more responsive than others.…”
Section: Neuropsychopathology Of Addiction -George and Koobmentioning
confidence: 99%
“…153 The G1258A polymorphism of the NPY gene has been linked to alcohol dependence. 154 The rs16147 SNP of the NPY promoter gene was linked to tobacco addiction. 155 Should a medication become available that modulates CRF or NPY, such genetic analysis may reveal that subpopulations of subjects who carry specific SNPs might be more responsive than others.…”
Section: Neuropsychopathology Of Addiction -George and Koobmentioning
confidence: 99%
“…Numerous studies have identified a number of single nucleotide polymorphisms that are associated with alcohol dependence and/or drug codependence including (a) CHRM2 (Luo et al, 2005; Wang et al, 2004), CHRNA4 (Kim et al, 2004), CHRNA5 (Saccone et al, 2007; Wang et al, 2009) as well as the CHRNA5-CHRNA3-CHRNB4 cluster and alcohol abuse/dependence (Schlaepfer et al, 2008); (b) DAT (Heinz, Goldman, Gallinat, Schumann, & Puls, 2004; see also Bhaskar & Kumar, 2014 for this and other DA-associated polymorphisms), DA beta hydroxylase (DBH) and alcohol dependence in women (Preuss et al, 2013), DRD3 and alcohol craving (Agrawal et al, 2013) as well as DA dysfunction and Cloninger Type I alcoholism (Leggio & Addolorato, 2008); (c) GABRA1, GABRA2, GABRB3, GABRG3 and alcohol dependence or sensitivity to its intoxicating effects during the ascending slope of the BAC curve (e.g., Bierut et al, 2010; Dick et al, 2004; Dick et al, 2006; Edenberg et al, 2004; Enoch, Schwartz, Albaugh, Virkkunen, & Goldman, 2006; Haughey et al, 2008; Noble et al, 1998); (d) GRIK3 (Grzywacz, Malecka, Suchanecka, Bienkowski, Samochowiec, 2013) and GRIN2A (Domart et al, 2012) with alcohol dependence as well as GRM8 and event-related potential (ERP) theta power and alcohol dependence (Chen et al, 2009); (e) 5HT dysfunction and Cloninger Type II alcoholism (Leggio & Addolorato, 2008), HTR1A and alcohol as well as nicotine co-dependence (Zuo et al, 2013), HTR1B and alcohol as well as multiple drug abuse (Cao, LaRocque, & Li, 2013; Contini et al, 2012), HTR2A and alcohol as well as heroin abuse (Cao et al, 2014), HTR7 and alcohol dependence as wel as electrophysiological measures (Zlojutro et al, 2010; Zuo et al, 2014), alcohol dependence and SERT (e.g., Heinz et al, 2004; c.f., Johnson, 2010; McHugh, Hofman, Asnaani, Sawyer, & Otto, 2010; Plemenitas et al, 2015); (f) OPRM1 and level of response to ethanol in Native Americans (Ehlers, Lind, & Wilhelmsen, 2008), OPRM1 polymorphisms and naltrexone’s efficacy for treating alcohol dependence (e.g., Jonas et al, 2014), as well as PDYN and OPRK1 with alcohol dependence (Gerra et al, 2007; Williams et al, 2007; Xuei et al, 2006); (g) CRFR1 polymorphism with P3 ERP and alcohol dependence (Chen et al, 2010); and (h) NPY and its receptor’s association with alcohol as well as multiple drug abuse and dependencies (Bhaskar et al, 2013; Frances et al, 2011; Okahisa et al, 2009; Sato et al, 2010; Wether...…”
Section: Pharmacogenomics and Alcoholism/addictionmentioning
confidence: 99%
“…One of the largest studies identified associations between SNPs in the NPY2 and NPY5 receptor genes with alcohol withdrawal symptoms (Wetherill et al, 2008). Other studies have identified SNPs in NPY to be associated with alcohol dependence or higher levels of alcohol consumption (Karvonen et al, 1998; Lappalainen et al, 2002; Bhaskar et al, 2013). In humans, a microarray study using postmortem tissue showed that NPY expression was reduced in the frontal and motor cortices of chronic alcohol drinkers relative to controls (Mayfield et al, 2002).…”
Section: Npymentioning
confidence: 99%